Rekayasa Mesin Pencacah Jerami Padi - Wahyu K. Sugandi; Zaida Zaida; Devi Maulida (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACTDesigning of Rice Straw Chopper MachineAccording to observations conducted in the field, the potential of straw wastes in Ciparay, Bandung, West Java Indonesia reaches 10-12 tons / ha but its utilization has not been optimazed to this date. After harvested, the remaining unused straw is abandoned on the ground and is eventually burned. In the long run, this straw burning will be very disadvantageous to farmers, especially in terms of the environmental impacts on rice paddy including decreasing soil fertility, killing soil biota, damaging soil physical properties and wasting energy. One of alternatives to utilize rice straw able to provide added value by utilizing its waste as a material to make compost on the condition that the straw should br chopped into a size of 5-10 cm according to SNI standards. Therefore, a study on rice straw chopping technology based on the composting requirements is required. The goal of this study was to design a prototype of rice straw chopper with capacity of 200 kg/hour. The method used in this research was engineering method including requirement observation, design criteria, functional and structural design, figure design, technical analysis, prototyping of rice straw chopper, machine functional and performance test. The measurement results of rice straw characteristics showed that the average length, diameter, bulk density and moisture content of rice straw are 708 mm, 4 mm, 160.6 kg/m3 and 34.6% wet basis. This straw chopper engineering produced a prototype with a dimension of 1040 mm (length) x 1000 mm (height) x 465 mm (width) with a power source generator using 5.5 HP gasoline motor. The result of functional test of the straw chopper showed that the actual capacity of this straw chopper was 100.32 kg/hour.Keywords: compost, prototype, functionalABSTRAKPotensi limbah jerami yang ada di Kecamatan Ciparay Kabupaten Bandung berdasarkan pengamatan di lapangan mencapai 10 – 12 ton/ha yang hingga saat ini pemanfaatannya belum optimal. Setelah panen, sisa jerami yang tidak terpakai disimpan begitu saja di lahan yang pada akhirnya dibakar. Pembakaran jerami ini dalam jangka panjang akan sangat merugikan petani karena terutama berdampak negatif bagi lingkungan di lahan sawah yang meliputi penurunan kesuburan tanah, mematikan biota tanah, merusak sifat fisik tanah dan pemborosan energi. Salah satu cara pemanfaatan jerami padi yang dapat memberikan nilai tambah yaitu dengan memanfaatkan limbah jerami padi sebagai bahan untuk membuat kompos dengan syarat bahwa jerami tersebut sudah dalam keadaan tercacah dengan ukuran 5 – 10 cm sesuai standar SNI. Oleh sebab itu diperlukan suatu penelitian teknologi pencacahan jerami padi sesuai syarat pembuatan kompos. Tujuan dari penelitian ini adalah merancang bangun mesin protipe mesin pencacah jerami padi dengan kapasitas 200 kg/jam. Adapun metode yang digunakan pada penelitian ini adalah metode rekayasa (engineering) yang meliputi observasi kebutuhan, kriteria rancangan, rancangan fungsional, rancangan struktural, gambar desain, analisis teknik, pembuatan protipe mesin pencacah jerami padi, uji fungsional mesin dan uji kinerja mesin. Hasil pengkuran terhadap karakteristik jerami padi menunjukkan bahwa rata panjang, diameter, bulk density dan kadar air jerami padi masing-masing adalah 708 mm, 4 mm, 160 kg/m3 dan 34,6% basis basah. Hasil rekayasa mesin pencacah jerami mempunyai dimensi panjang 1040 mm, tinggi 1000 mm dan lebar 465 mm dengan sumber tenaga penggerak menggunkan motor bensin 5,5 HP. Hasil pengujian fungsional terhadap mesin pencacah jerami menunjukkan bahwa kapasitas aktual mesin penacacah jerami padi adalah 100,32 kg/jam, dengan panjang potongan < 5 cm.Kata Kunci : Kompos, Prototipe, Fungsional